Rules, Power and Trust - Jelle Koolwijk (A+BE: Architecture and the Built Environment)
The aim of this PhD project was to explore the multi-level interplay between the interorganizational structures and interpersonal relations in building project organizations. In the first two studies, quantitative approaches were used to validate assumptions about how interorganizational structures are shaped by actors and how interpersonal relationships affect the effectiveness of project teams in the construction industry. These two studies were integrated in a third qualitative case study that explored the interplay between inter-organizational structures and interpersonal relationships in long-term partnerships. The third study sampled three cases of strategic partnerships which are characterized as longterm, highly integrated and collaborative relationships. To gain theoretical sensitivity in this thirdstudy, a conceptual framework was developed using the concepts from the first two studies. The major finding across the three studies is that the way integration in the supply chain develops is highly dependent on the interaction between project actors. The way actors use the interorganizational rules of a project organization, influences the level of trust and no-blame culture that emerges through interaction. In turn, the level of trust can influence the rules of actors. More specifically, dominant actors seem to able to change the rules of the system. When a dominant actor uses his power position to change the rules of the social system, it can make other actors lose their commitment to the partnership. This research shows that successful long-term and close collaboration between firms continuously requires careful consideration of how the organizational structures are designed and used and their effect on relationships between actors. One should not assume that integrated contracts and integrative practices that have been shown to work in one project, will automatically lead to close and long-lasting relationships between actors in another project.